Effectiveness of a holistic neuropsychological rehabilitation program using virtual reality - Liliana Mendes; Luís Paulo Reis; Fernando Barbosa (PsychTech & Health Journal)
Acquired brain injury (ABI) is associated with severe functional consequences at several levels: personal, psychological, social, physical, economic, and systemic. The main objective of the present study is to show the potential of applying virtual reality (VR) in neuropsychological rehabilitation and the consequent psychological and cognitive improvement of the person with ABI. A total of 27 participants of both sexes with moderate or severe ABI participated in an investigation in a clinical trial-type design with pre-test and post-test. Participants in the experimental group (n = 8) underwent a remote holistic neuropsychological intervention program supported by a VR platform: the Virtual Centre for the Rehabilitation of Road Accident Victims (VICERAVI). The experimental group results were compared with a first control group (n = 10) that underwent a conventional holistic neuropsychological intervention face-to-face program. A second control group did not have any neuropsychological intervention (n = 9). We conclude that the VR-based neuropsychological rehabilitation program (NRP) at a distance produces better cognitive results in general cognitive functioning, learning, memory, and executive functioning than the conventional face-to-face NRP. Still, the conventional NRP obtained results similar to those of the VR-based NRP, which did not produce significant improvements at the psychosocial level. Thus, the study results suggest that the development of VR-based holistic NRPs may benefit the autonomy of people with ABI.